INFLUENCE OF FEAR OF FALL ON BALANCE AMONG COMMUNITY DWELLING OLDER ADULTS- LITERATURE REVIEW - KIRUTHIKA.S; C M RADHIKA (International Journal of Pharma and Bio Sciences, 2016)
Falls are one of the most common and problematic issues among older adults. In spite of falls in elderly, there is higher prevalence of Fear of Falling in people with falls (40-73%) and even in people without any history of falls. Tinetti and Powell described fear of falling as an ongoing concern about falling that ultimately leads to avoidance of performance of daily activities. Though there are various preventive and intervention programs used to reduce Fear of Falling, its influence on balance or postural control is limited. A study in 2008 concluded that fear of falling has significant association on balance and functional mobility in community dwelling older adults. Fletcher and Hiredes showed the positive correlation between balance deficit/mobility and the fear of falling. To analyze the influence of Fear of Fall on Balance among community dwelling older adults Literature was collected over past 20 years. Study materials was collected through direct science, pubMed, Elesiver, Embase, Wiley online library and Google scholar. Studies that used various scales to measure fear of falling and balance were also considered Results show that Fear of Falling is prevalent in older adults regardless of age or gender. Fear of falling does have influence on Balance among community dwelling older adults.